Children in Australian families - Ochiltree, Gay. (Malaysia : Longman Cheshire Pty Ltd, 1990)
The focus of this book is on children within the context of the family, and the emphasis is on the social aspects of childhood. This book discusses some of these changes and their effects on children.
Keywords: Australia; Family; Children; Children -- Australia -- Juvenile literature